[Groin pain in sports games: a systematic review]. - Zilles, Gabriel; Grim, Casper; Wegener, Florian; Engelhardt, Martin; Hotfiel, Thilo; Hoppe, Matthias Wilhelm (Sportverletzung-Sportschaden, 2023)
BACKGROUND: In sports games, epidemiological data show that groin pain is relatively common and can lead to repeated loss of time. Consequently, it is essential to be aware of the evidence-based prevention strategies. The aim of this systematic review was to examine risk factors and prevention strategies for groin pain and to rank them based on their evidence in sports games. METHODS: The review was conducted according to the PRISMA guidelines, using a PICO-scheme in the PubMed, Web of Science and SPOLIT databases. We included all available intervention and observational studies on the influence of risk factors and prevention strategies on groin pain in sports games. The methodological quality and level of evidence was assessed using the PEDro-Scale and OCEBM model, respectively. Finally, the quantity, quality and level of evidence was used to rank each risk factor for its grade. RESULTS: Moderate evidence was found for four risk factors that significantly influence the risk of groin pain: male sex, previous groin pain, hip adductor strength and not participating in the FIFA 11+ Kids. Moreover, moderate evidence was found for the following non-significant risk factors: older age, body height and weight, higher BMI, body fat percentage, playing position, leg dominance, training exposure, reduced hip abduction, adduction, extension, flexion, and internal rotation-ROM, hip flexor strength, hip abductor, adductor, flexor and core strengthening with balance exercises, clinical hip mobility tests and physical capacities. CONCLUSION: The identified risk factors can be considered when developing prevention strategies to reduce the risk of groin pain in sports games. Thereby, not only the significant, but also the non-significant risk factors should be considered for prioritisation.
EVALuna2:594931